2014
DOI: 10.1002/humu.22533
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance to Malaria in Mice with Methylenetetrahydrofolate Reductase (Mthfr) Deficiency Suggests a Mechanism for Selection of theMTHFR677C>T (c.665C>T) Variant

Abstract: The polymorphism 677C>T (NM_005957.4:c.665C>T/p.Ala222Val, rs1801133:C>T) in methylenetetrahydrofolate reductase (MTHFR) results in mild enzymatic deficiency and increased risk for several complex traits including adverse reproductive outcomes, birth defects, and heart disease. Despite these deleterious effects, homozygosity is high (5%-15%) in many populations, and among the highest in Mediterranean regions, where malaria was historically endemic and may have conferred a selective advantage for other mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 37 publications
(47 reference statements)
3
17
0
Order By: Relevance
“…MTHFR mice survived longer than MTHFR overexpressing mice. 17 A similar result was obtained earlier in the knockout mice (Mthfr −/− mice) to cytomegalovirus. 31 The data clearly suggests that mild MTHFR deficiency protects against severe malaria and that this phenomenon may have led to the high frequency of the C677T variant in human populations across the world.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…MTHFR mice survived longer than MTHFR overexpressing mice. 17 A similar result was obtained earlier in the knockout mice (Mthfr −/− mice) to cytomegalovirus. 31 The data clearly suggests that mild MTHFR deficiency protects against severe malaria and that this phenomenon may have led to the high frequency of the C677T variant in human populations across the world.…”
supporting
confidence: 82%
“…16 A recent study in experimental mice has clearly shown that mild MTHFR deficiency protects from malaria which provides further evidence for the hypothesis that this polymorphism has been subjected to selection pressure in malaria endemic regions. 17 Not many studies are available on the general prevalence of other single nucleotide polymorphisms (SNPs) in the genes involved in folate metabolism pathway. The disease association studies with the variants of folate metabolism are also few, but it is possible that gene-gene interactions may exist among the SNPs in the folate metabolism pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Both the main MTHFR variants have been indicated as a possible resistance factors to colon cancer [69] and to metastases of myeloid leukaemia [70], just to quote some examples. In addition, the proliferation of the plasmodium of malaria is far less efficient in presence of a defective MTHFR and this may explain the high prevalence of these genes in the Mediterranean area [71]. In conclusion, a subject carrying a MTHFR variant that is well compensated by the diet and by the pattern of associated genetic variants of the other metabolic enzymes may have a selective advantage compared to what is considered a “normal” genotype.…”
Section: Introductionmentioning
confidence: 99%
“…In Colombia, some studies show a predominance of allele C and others of allele T. Differences between populations suggest that both allele frequencies in certain circumstances could produce selective advantages and disadvantages. Some reports suggest that the T allele can produce resistance to infections such as malaria and cytomegalovirus and may also protect against hypertension 32 , 33 . Similarly, the C allele protects against birth defects and cancer and is associated with higher fertility and relatively late onset of neurological diseases 34 .…”
Section: Discussionmentioning
confidence: 99%